G45 What is the association between epistaxis and asphyxiation in children under 2 years? a systematic review. (27th April 2015) - Rees, P; Kemp, A; Dunstan, F; Carter, B; Maguire, S
Abstract : Aims: Whilst epistaxis is a frequent and trivial finding in most children, it is rare in those aged less than 2 years. Epistaxis has been observed amongst intentionally asphyxiated infants using covert surveillance, although the precise relationship between epistaxis and asphyxia has subsequently been called into question. This systematic review aims to determine the probability of asphyxia amongst young children presenting with epistaxis, and define the clinical characteristics of such children. Methods: An all-language search of published and grey literature across 10 databases from 1900–2014 was conducted with 76 key terms. Searches were supplemented with 'snowballing' techniques including hand searching non-indexed journals, checking articles' references, and correspondence with authors for clarification. Inclusion criteria: high quality studies involving children with epistaxis aged less than 2 years; alive or dead on presentation; adequate confirmation or exclusion of intentional or unintentional asphyxia (upper airway obstruction), using an explicit rank of confirmation of asphyxia and non-asphyxia. Studies of traumatic or pathological epistaxis were excluded. All studies were independently critically appraised and data extracted by two trained reviewers. The probability of asphyxiation in a young child with epistaxis was estimated in a meta-analysis using a random-effects model and is reported as a proportion with 95% Confidence Intervals (CI). Results: Of 2549 studies identified, 100 underwent full review, resulting in six included studies, representing 30 children with asphyxia-related epistaxis and 74 non-asphyxia related epistaxis. Meta-analysis was feasible for 4 studies yielding a probability of asphyxiation of 20% (95% CI = 13–29%). Children with asphyxia-related epistaxis were aged 30–684 days and described by 2 comparative cross-sectional studies, 1 case-control study, and 3 case series (1 of which was comparative). Live asphyxiated children tended to present unwell with altered skin colour, respiratory difficulty, and chest X-ray abnormalities. There were no associated features described among those dead on arrival. Conclusion: This systematic review defines the probability that epistaxis, in the absence of trauma or medical explanation, may indicate asphyxia in children aged less than 2 years, thus reiterating the importance of full investigation of these children who may be at considerable risk of death.